Applied Informatics and Communication International Conference, ICAIC 2011, Xi'an, China, August 20-21, 2011, Proceedings, Part IV - Zhang, Jun (Springer eBooks., 2011)
The five volume set CCIS 224-228 constitutes the refereed proceedings of the International conference on Applied Informatics and Communication, ICAIC 2011, held in Xi'an, China in August 2011. The 446 revised papers presented were carefully reviewed and selected from numerous submissions. The papers cover a broad range of topics in computer science and interdisciplinary applications including control, hardware and software systems, neural computing, wireless networks, information systems, and image processing.